Abusive supervision, psychological distress, and silence: the effects of gender dissimilarity between supervisors and subordinates - Park, Joon Hyung; Carter, Min Z.; DeFrank, Richard S.; Deng, Qianwen (Springer Netherlands, 2016)
Previous research has shed light on the detrimental effects of abusive supervision. To extend this area of research, we draw upon conservation of resources theory to propose (a) a causal relationship between abusive supervision and psychological distress, (b) a mediating role of psychological distress on the relationship between abusive supervision and employee silence, and (c) a moderating effect of the supervisor–subordinate relational context (i.e., gender dissimilarity) on the mediating effect of abusive supervision on silence. Through an experimental study (Study 1), we found the causal path linking abusive supervision and psychological distress. Results of both the experimental study and a field study (Study 2) provided evidence that psychological distress mediated the relationship between abusive supervision and silence. Lastly, we found support that this mediation effect was contingent upon the relational context in Study 2 but not in Study 1. We discuss implications for theory and practice.